5,5?-Pyridine-2,6-diylbis[4-ethyl-2,4-dihydro-1,2,4-triazole-3(2H)-thione] - Demir, Sibel; Dincer, Muharrem; Cetin, Ahmet; Dayan, Osman; Cansiz, Ahmet (Int Union Crystallography, 2006)
In the title compound, C13H15N7S2, the two triazole rings are twisted away from the central pyridine ring by 11.7 (2) and 41.8 (1)degrees. Inversion-related mol-ecules are linked by N-H center dot center dot center dot S hydrogen bonds, forming dimers which are linked into a chain by N-H center dot center dot center dot N hydrogen bonds.